PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI DAN SUMBER INFORMASI TEREKAM PADA UKM BATIK BAMBU KENANGA - Farika Nikmah; Musthofa Hadi; Kartika Indah Permanasari (Dharma: Jurnal Pengabdian Masyarakat, 2023)
The role of social media is currently developing not only as a means of showing oneself or proof of existence. However, business people are starting to use social media as a promotion, because this media offers low costs with a wide market reach. Not only as promotional media, social media  can also be used as document storage in an orderly and chronological manner, according to the time at which the documents were made. This is the aim of this activity, which is to maximize the role of social media for batik SMEs. Relatively low cost, easy operation (can be done via HP), and does not require skills that must be experts in the IT field. This activity was carried out at Batik Bambu Kenanga, located in Turen District, Malang Regency, East Java. The results show that the guidance and training provided was very useful and taught Batik Bambu Kenanga to compile promotional content as well as archive important documents, especially the batik products they produce.